2022-RA-1256-ESGO First experiences of implementing 'enhanced recovery after surgery' (ERAS) at two German ESGO centers of excellence – KORE-INNOVATION: the first prospective clinical trial to assess a perioperative pathway to reduce postoperative complications in ovarian cancer patients. (20th October 2022) - Inci-Turan, Melisa Guelhan; Schneider, Stephanie; Schnura, Eva; Lee, Marlene; Lauseker, Marcus; Klews, Julia; Lohrmann, Renée; Baack, Angelika; Meinert, Fabian; Zwanzleitner, Lena; Roll, Stephanie; Reinhold, Thomas; et al.
Abstract : Introduction/Background: The perioperative ERAS pathway has been established in many surgical fields and has shown to improved health care quality and costs. We report our first experiences implementing the ERAS pathway as part of the KORE INNOVATION trial in patients with ovarian cancer. Methodology: KORE INNOVATION is an ongoing clinical trial to assess the effects of an innovative perioperative care pathway to reduce complications for patients undergoing surgery for ovarian cancer by implementing a prehabilitation strategy combined with an ERAS pathway. The trial is conducted at two study sites in Germany, both ESGO centers of excellence for ovarian cancer surgery: Charité Universitätsmedizin Berlin and Evangelische Kliniken Essen Mitte. ERAS guidelines were adapted for the clinical settings, and multiple training sessions for all staff were conducted. An interdisciplinary 'KORE-team' consisting of physicians, nurses, nutritionists, and physiotherapists was established to aid implementation, monitor staff adherence, follow the patients throughout the entire care process, and function as interface managers. We report our first experiences with the staff's adherence to ERAS items at both study sites. Results: The following ERAS items showed good adherence: omission of bowel preparation, carboloading, disinfection using chlorhexidine, use of opioid-sparing anesthesia and epidurals, early postoperative mobilization, and feeding. In contrast, the following items showed decreased adherence: omission of pre-operative sedatives, omission of drains, goal-oriented fluid management during the postoperative phase, and the omission of postoperative antibiotic treatment. Adherence increased through monitoring through daily rounds and active staff engagement administered by the KORE team. Conclusion: Continuous training and adherence monitoring are by multi professional and interdisciplinary KORE team are key factors for the successful implementation of the ERAS pathway.